2001
DOI: 10.1177/021849230100900202
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Sternal Closure after Cardiac Operations

Abstract: In 1,459 open heart operations performed between July 1995 and March 2000, sternal closure was delayed in 30 patients (2%) because of hemodynamic instability limiting primary sternal closure in 12 and uncontrollable bleeding in 18. Two patients died in the immediate postoperative period while the chest was open, due to persistent low cardiac output secondary to myocardial failure. The sternum was closed in 28 patients at an average of 22 ± 0.3 hours (range, 8 to 48 hours) postoperatively. Two patients died in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Prolonged open sternotomy with subsequent DSC has been described as useful in the treatment of server myocardial dysfunction, uncontrollable hemorrhage, and intractable arrhythmia 7,15‐17 . These effects are magnified in the presence of poor ventricular compliance secondary to ischemia, reperfusion, and myocardial edema 18 . Restriction of diastolic filling is the main point at which there is disproportion in the cardiac to mediastinal relationship, leading to compression or tamponade 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged open sternotomy with subsequent DSC has been described as useful in the treatment of server myocardial dysfunction, uncontrollable hemorrhage, and intractable arrhythmia 7,15‐17 . These effects are magnified in the presence of poor ventricular compliance secondary to ischemia, reperfusion, and myocardial edema 18 . Restriction of diastolic filling is the main point at which there is disproportion in the cardiac to mediastinal relationship, leading to compression or tamponade 19 .…”
Section: Discussionmentioning
confidence: 99%
“…[1] These effects are amplified by poor ventricular compliance due to myocardial edema and ischemia-reperfusion injury. [2] Furnary et al . have shown that opening sternum raises systemic blood pressure by 18% and cardiac index by 59% and thereby beneficial in improving low cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Primary sternal closure carries a mortality of 8.7%, superficial sternal infection in 13.3%, mediastinitis 1.2% and sternal dehiscence in 3.7% 21 . Deep sternal wound infection increases morbidity and mortality 22 , in cardiac surgery choosing a proper approach for a given procedure is a must, because even with minimally invasive cardiac procedures serious wound infections can occur 23 .…”
Section: Jmscr Vol||3||issue||9||page 7377-7384||september 2015mentioning
confidence: 99%